2019
DOI: 10.4034/pboci.2019.191.81
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Incidental Findings on Cone Beam Computed Tomography

Abstract: Objective: To assess the prevalence of incidental findings in relation to the side of a patient's face, location, and age group on cone beam computed tomography. Material and Methods: 175 CBCT examinations were performed on patients aged between 12 and 77 years, consisting of recordings of the anatomical location and findings following each examination. For standardization of tomographic evaluations, acquired images were analyzed by two previously trained expert radiologists. After positional adjustment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…IFs can be due to several factors, such as allergies, anatomical variations, or even the first signs of serious diseases [15,23]. Underdiagnosis can be of concern since not identifying or ignoring an IF can cause harm to the patient.…”
Section: Impact Of Ifs On Patient's Livesmentioning
confidence: 99%
“…IFs can be due to several factors, such as allergies, anatomical variations, or even the first signs of serious diseases [15,23]. Underdiagnosis can be of concern since not identifying or ignoring an IF can cause harm to the patient.…”
Section: Impact Of Ifs On Patient's Livesmentioning
confidence: 99%
“…Most of the studies included in the meta-analysis were conducted in adults, 6 studies were conducted in pediatric cohorts, 4,10,[17][18][19][20] and 10 studies 8,[21][22][23][24][25][26][27][28][29] were in a mixed patient cohort. The breakdown of the 33 studies into population groups was as follows: 1 study in group 1 (specific symptom screening with endoscopy), 16 in group 2 (specific symptom screening without endoscopy), and 16 in group 3 (no specific screening).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six of the 33 studies 21,23,[31][32][33][34] included in the metaanalyses elsewhere did not state their cutoff for classifying significant mucosal thickening but reported a combined prevalence of 21.3% of some degree of thickening. Nine of the studies excluded from the meta-analysis due to incomplete data found a combined 12.8% prevalence of some degree of maxillary sinus mucosal thickening.…”
Section: Maxillary Sinus Mucosal Thickening 2 MMmentioning
confidence: 99%